The Effect of Automation on Job Performance Elements and Job Security of Sweet Industry Workers: An Application in Jordan - ALABSİ, SADAM (İstanbul Kültür Üniversitesi, 2023)
This research presents a better understanding of the effect of Automation on job performance elements and job security for better-managing employees' job security and performance in the sweet sector in Jordan. The research population was the sweet companies in Jordan. One hundred seventy-four organizations were considered as the research population. The research adopted a quantitative approach, and the data was obtained via a non-probability purposive selection sampling technique. Questionnaires were distributed by emails; 184 were filled. Data analyses were performed, and the results were revealed using descriptive statistics, correlation, and multiple regression analysis techniques. The research findings provided conclusions about the effect of Automation on the employees' perception of job security and job performance. The findings showed strong correlations among Automation, employee job security, and job performance elements. Automation was inversely and significantly related to job security and positively and significantly to job performance elements. This research assists businesses in general and sweet organizations in particular in understanding the influence of Automation on employee job security and job performance elements and therefore managing better employees in the workplace, which will significantly assist in improving ideal work conditions. Future studies can concentrate on organizational and operational performance. Moreover, further research may investigate the impact of the mediation of organization policies and practices.
Tatlı Endüstrisideki Otomasyonun, Çalışanlarının İş Performansı Etkileyen Unsurlarına ve İş Güvenliğine Etkisi: Ürdün'de Uygulanan Bir Uygulama
▪ Yüksek lisans tezi.
Keywords: Automation; Job Security; Job Performance; Measurability; Understandability; Achievability